Practical research 1 - Balaoing, Joseph G. (Sampaloc, Manila : Rex Book Store, Inc., 2022)
"Practical research 1 is part of a two-worktext series in Practical Research designed for Grade 11 learners to introduce them to the exciting world of discovery, exploration, and unraveling of phenomena that can give light and bring solutions to problems in society through qualitative research. It is anchored on the K-12 curriculum of the Department of Education and organized in a manner that ensures a safe, healthy, engaged, supported, and values-oriented learning experience. It is organized inductively starting with everyday experiences and gradually developed into full-blown concepts of qualitative research. Easy-to-follow steps and concrete examples are provided to serve as a ready-made template for writing. The activities and assessments flow naturally from the concepts to measure learning and skill leading toward the actual writing of a research paper. This book provides a wide array of examples from different disciplines to promote awareness of social issues and create a venue to practice objectivity, reflexivity, critical thinking, problem-solving, decision-making skills, and creativity. Above all, Practical Research 1 is an easy companion in writing a qualitative research replete with full discussion of concepts, concrete examples and easy-to-follow steps".
Includes bibliographical references.
English text.
Keywords: Research -- Methodology